How Do Marine Mammals Manage and Usually Avoid Gas Emboli Formation and Gas Embolic Pathology? Critical Clues From Studies of Wild Dolphins - Fahlman, Andreas; Moore, Michael J.; Wells, Randall S. (Frontiers in Marine Science, 2021)
Decompression theory has been mainly based on studies on terrestrial mammals, and may not translate well to marine mammals. However, evidence that marine mammals experience gas bubbles during diving is growing, causing concern that these bubbles may cause gas emboli pathology (GEP) under unusual circumstances. Marine mammal management, and usual avoidance, of gas emboli and GEP, or the bends, became a topic of intense scientific interest after sonar-exposed, mass-stranded deep-diving whales were observed with gas bubbles. Theoretical models, based on our current understanding of diving physiology in cetaceans, predict that the tissue and blood N2 levels in the bottlenose dolphin (Tursiops truncatus) are at levels that would result in severe DCS symptoms in similar sized terrestrial mammals. However, the dolphins appear to have physiological or behavioral mechanisms to avoid excessive blood N2 levels, or may be more resistant to circulating bubbles through immunological/biochemical adaptations. Studies on behavior, anatomy and physiology of marine mammals have enhanced our understanding of the mechanisms that are thought to prevent excessive uptake of N2. This has led to generation of a new hypothesis, the selective gas exchange hypothesis, as to how stress-induced behavioral change may cause failure of the normal physiology, which results in excessive uptake of N2, and in extreme cases may cause formation of symptomatic gas emboli. Studies on cardiorespiratory function have been integral to the development of this hypothesis, with work initially being conducted on excised tissues and cadavers, followed by studies on anesthetized animals or trained animals under human care, participating voluntarily. These studies then enabled research on free-ranging common bottlenose dolphins in Sarasota Bay, FL, and off Bermuda, and have included work on the metabolic and cardiorespiratory physiology of both shallow- and deep-diving dolphins and have been integral to better understand how cetaceans can dive to extreme depths, for long durations.